Analysis of the Effect of Adding Concrete Waste as Cement Substitution on the Compressive Strength of Mortar - Ahmad Fathoni; Ali Fahmi Sidik; Ridta Dwi Septyan (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Development or construction activities are one of the sectors with the largest and very massive use of materials, especially cement and concrete. One of the efforts to reduce the negative impact of the use of excess materials and for the long-term sustainability of construction is the choice of recycled materials, in this case concrete waste as a cement substitution in the mortar aggregate mixture. Mortar is a non-structural building material component is a mixture consisting of cement, fine aggregate, and water that functions as a binding agent. The selection of concrete waste as a substitute material for cement in mortar mixtures is because concrete waste is a material that is very easy to find in the construction industry and has a high potential for repeated use. The research method used was a laboratory experiment by testing mortar samples measuring 5cm x 5cm x 5cm with a mixed portion of 1PC:3PS. The mixture design is calculated and measured with each mixture of water, cement and fine aggregate or sand, then substitution is carried out by reducing the volume in the cement by a percentage of 0%, 5%, 10%, 15%, 25% and 30% respectively. Mortar compressive strength testing is carried out at the age of the mortar test piece reaching 7, 14,21, and 28 days with maintenance. The results of the study on the compressive strength of mortar with a reference of normal/control test pieces (0%) with a value of 30.67Mpa with a treatment age of 28 days, a significant decrease was obtained in the proportion of the substitution mixture of 25% and 30% respectively 24.67Mpa (19.56% decrease) and 25.33Mpa (17.41% decrease), the decrease was still within normal limits in the substitution mixture of 5%, 10%, 15% and 20%, with values of 28Mpa, 28.67Mpa, 29.33Mpa and 29.33Mpa. The values closest to the baseline were a mixture of 15% and 20%, respectively 29.33Mpa or 4.37% decrease with the same treatment age of 28 days.